Emotion in dialogic interaction : advances in the complex - Weigand, Edda (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2004)
This volume contains a selection of papers given at the European Science Foundation Exploratory Workshop on 'Emotion in Dialogic Interaction' at the University of Münster in October 2002. In the literature, the complex network of 'emotion in dialogic interaction' is mostly addressed by reducing the complex and separating emotions or defining them by means of simple artificial units. The innovative claim of the workshop was to analyse emotion as an integrated component of human behaviour in dialogic interaction as demonstrated by recent findings in neurology and to develop a linguistic model wh.